PISA МАТЕМАТИКАЛЫҚ САЎАТЛЫЛЫҚ БАҒДАРЫ ТАПСЫРМАЛАРЫНЫҢ ДҮЗИЛИСИ ҲӘМ ОНЫ БАҲАЛАЎ УСЫЛЛАРЫ - Турманов, Қ. (ILIM hám JÁMIYET, 2021)
This article provides information according to the International assessment program PISA, its main directions, content, and structure of tasks to determining mathematical literacy, and also there are given recommendations for preparing for this program.